Comparative Study of Polygamy in the Marriage Law Based on Islamic Law and Feminism Perspective - Masrofah Masrofah; Selamat Widodo; Yusuf Saefudin (Universitas Muhammadiyah Sumatera Utara, 2026)
This study examines the extent to which Islamic legal norms regard polygamy as a permissible marital practice, and how feminist legal perspectives assess such practice within the framework of gender equality and the protection of women’s rights. The research is directed by two principal legal questions: (1) What is the comparative analysis of polygamy under the Marriage Law when viewed from the standpoint of Islamic Law and Feminist Legal Theory? and (2) How is the concept of justice for women subjected to polygamous marriages assessed under Islamic Law and Feminist perspectives? This study employs a normative legal research design using a qualitative descriptive analysis. Data were obtained through a literature-based method involving statutory materials, authoritative legal texts, scholarly works, and relevant academic articles. An analytical approach was adopted to interpret the meaning and scope of terms contained in legislative provisions, while data collection was conducted through comprehensive doctrinal and literature review to assemble all relevant legal information. The findings of this research demonstrate both differences and points of convergence between Islamic Law and Feminist perspectives regarding the legal and ethical status of polygamy. Under Islamic Law, polygamy is deemed permissible subject to strict substantive and procedural conditions, including the husband’s ability to uphold justice among his wives, both materially and emotionally. In practice, however, the failure to fulfil the principle of justice often results in discrimination and harm toward women. Conversely, from a Feminist perspective, polygamy is viewed as an inherently inequitable institution that reinforces patriarchal structures and places women in subordinate positions, socially, economically, and emotionally. Therefore, in order to achieve justice from both legal and gender-equality standpoints, a reinterpretation and reassessment of existing marital regulations is necessary to ensure greater responsiveness to gender justice and stronger protection of women’s rights.